COASTAL WOMEN EMPOWERMENT THROUGH PROCESSING OF FISHERY PRODUCTS IN TERNATE CITY - Misrina Misrina; Santoso Tri Rahardjo; Binahayati Rusyidi; Budhi Gunawan (Sosiohumaniora, 2022)
This article reports women’s empowerment activities in a fishery product processing program in Ternate City. Groups are assessed, not in terms of their success in producing fishery products and the impact on increasing the income of coastal families, from an economic perspective, but in terms of women’s contribution and participation to women’s empowerment in the program. This research uses a descriptive qualitative approach with data collection techniques carried out through in-depth interviews, observations and literature studies. Evidence emerged that women were only involved in the program implementation process. They are not involved in the process of determining women’s basic needs in fishery business diversification, planning, monitoring and program evaluation stages. When considered in the construction of empowerment and democratization processes. Coastal women have not been involved as subjects in a fishery product processing program that aims to free them from poverty through various business trainings. As well as the cultural influence of coastal communities who still live in the customs of the Sultanate of Ternate. So that the results of the program based on the perspective of women’s empowerment do not contribute to the critical awareness of coastal women so that an inclusive and equitable model of coastal women’s intervention is needed and pays attention to social and cultural structures.